Distilling a body of knowledge for information systems development. (18th January 2017) - Hassan, Nik Rushdi; Mathiassen, Lars
Abstract: As a contribution towards consolidating the information systems (IS) field, we offer a systematic method for distilling a canonical body of knowledge (BOK) for information systems development (ISD), an area that historically accounts for as much as half of all IS research. Based on an integrative synthesis of the literature, we present a map of the most significant ISD research, uncover gaps in its canons and suggest fruitful lines of inquiry for new research. Our review combines citation analysis, which identifies the field's evidence of cumulative tradition, with computer‐aided textual analysis, a hermeneutically guided method that organizes the fragmented corpus of ISD literature into coherent knowledge areas. From a pool of over 6500 articles published in the IS Senior Scholars' Basket of Journals, we find 940 IS citation classics, and from that list, 466 ISD articles that offer canonical ISD knowledge distinctive to IS and complementary to other disciplines such as software engineering and project management. From this study, we offer two contributions: (1) a justification for an ISDBOK grounded in the theory of practice and professionalism, and (2) a canonical map of disciplinary ISD knowledge with areas that have demonstrated cumulative tradition and others that require the attention of IS scholars. © 2017 John Wiley & Sons Ltd